Edukasi Penulisan Puisi dalam Meningkatkan Kreatifitas Siswa di Desa Rawaapu - Hidayat Nurseptiadi; Lutfi Eskawati; Estri Dwi Astuti (Biro Pengelolaan Penelitian dan Pengabdian Kepada Masyarat SETIA Ngabang, 2025)
The concept of poetry writing education in increasing students' creativity is basically directed at the formation of attitudes, so that there is a balance of children's intellectual, intellectual, mental, physical and moral, because at the age of junior high school, children's mental and physical development is in a high stage of development so that to optimize their creativity, education in writing poetry is one of the right ways to use. Therefore, poetry writing education should be a forum or means for children to develop and pour their creativity. Children's creativity at the age of Junior High School is still very diverse according to their level of maturity and brain development. To improve the development of children's creativity so that they grow optimally, education in writing poetry plays a very important role, namely as a means of facilitating children in expressing the child's thoughts and soul.